Cell-free DNA: plays an essential role in early diagnosis and immunotherapy of pancreatic cancer - Wen, Yi; Zhao, Gengmin; Dai, Chunhua (Frontiers in Immunology, 2025)
Pancreatic cancer is renowned for its aggressive nature and dismal prognosis, with the majority of patients diagnosed at an advanced stage. The prognosis for patients with pancreatic cancer can be improved by early diagnosis and effective treatment. Circulating cell-free DNA (cfDNA) has emerged as a promising biomarker for the early diagnosis and monitoring of pancreatic cancer. This research presents a review of circulating cell-free DNA essential role in the early diagnosis and immunotherapy of pancreatic cancer. The detection methods of cfDNA, its potential as a diagnostic biomarker, and the latest research progress in cfDNA-based immunotherapy are discussed. The findings suggest that cfDNA plays a vital role in the early detection and personalised treatment of pancreatic cancer, holding great promise for improving patient outcomes.